Penerapan Enterprise Resource Planning (ERP) Pengadaan Bahan Baku dan Pengelolaan Produksi Pada Perusahaan Furniture Menggunakan ADempiere (Studi Kasus: CV Roland Kencana) - Hasdi Putra; Ravi Azhari (Jurusan Sistem Informasi, Fakultas Teknologi Informasi, Universitas Andalas, 2016)
In this era of global competition, companies need to shorten the production cycle, responsive to market dynamics and customer demand and to strengthen information exchange system. In this competitive environment, Enterprise Resource Planning (ERP) is very helpful in integrating the management of all the company's resources. In manufacturing companies such as furniture, raw materials shall be made available for the production process. Shortages of raw materials can be anticipated early through inventory information that can be accessed quickly and accurately so that the business process is still running. This study aims to assist companies in implementing ERP systems by proposing strategies and tactics to overcome the problems encountered in implementing ERP systems. ADempiere as one ERP applications can help manage the transaction data and inventory business processes to improve corporate performance. The stages are carried out in this research is to identify problems, analyze business processes, election ADempiere application modules, implementation and testing of applications. Business processes are identified consisting of sales, purchasing and production. The results of analysis of business processes described in the Business Process Modeling Notation (BPMN) and a working model of the system is shown by the use case diagram. System test results obtained by comparing the ERP system using the manual system. The test results prove that ADempiere can produce the raw material inventory information in real time, generate transaction reports purchases, sales, production, and financial reports automatically so that it can help company leaders make decisions quickly and accurately.